Bus timetabling considering passenger satisfaction: An empirical study in Beijing. (September 2019) - Shang, Hua-Yan; Huang, Hai-Jun; Wu, Wen-Xiang
Highlights: Conduct an empirical study in Beijing. Formulate passenger satisfaction addressing waiting time and on-board discomfort. Propose a practical timetabling with a compromise of efficiency and satisfaction. Abstract: Public transport is the key component in sustainable transportation. In China, large subsidies are provided by the national and local governments to encourage the use of public transport systems. However, high commuting demand leads to such incredible phenomenon that passengers have to climb windows for riding in buses during peak hours. Thus, a case study was conducted in a Beijing's transport hub which covers 116 bus lines and ten stations. The existing bus timetabling is surprisingly manually made and 26.53% of the bus supply undertakes 59.19% of the bus demand, which results in unbearable long waiting time and on-board crowding. To find a bus timetabling method which is practical and applicable in China, three procedures are carried out. Firstly, the passenger satisfaction and the bus transit efficiency are simplified and formulated. Secondly, a preliminary bus timetabling method with consideration of passenger satisfaction is proposed for optimizing the bus frequency and headway. Thirdly, the bus timetabling is optimized by embodying a balance between the passenger satisfaction and the bus transit efficiency, subject to the constraints of load factor. This method is verified by field data and the results demonstrate that it has the advantage of reducing waiting time and lessening on-board discomfort.